China's oil diplomacy: is it a global security threat? - Lai, Hongyi (Taylor & Francis, 2007)
China is now the world's second largest oil consuming nation. China's external quest for oil has thus generated much attention and is believed by many to destabilise the world order. This article attempts to provide an overview of China's external initiatives for satisfying domestic oil demands and to examine the implications of China's oil diplomacy on regional and global political stability. The article suggests that China has taken three steps to satisfy its growing domestic demand for oil—expanding overseas oil supplies from the Middle East, diversifying its importing sources by reaching out to Africa, Russia, Central Asia and the Americas, and securing oil transport routes. This article argues that China's oil diplomacy strengthens its ties with oil-producing nations and complicates those with oil-importing nations. Nevertheless, contrary to pessimistic predictions, China's oil diplomacy has neither upset the USA's fundamental policies towards Iraq and Iran, nor has it generated armed clashes in the South China Sea. China has largely accommodated the USA in these areas and has forged joint efforts in energy exploration with its Asian neighbours, except for Japan. China's benign oil diplomacy can be explained by the minor role of oil imports in its energy consumption and, more importantly, by China's peaceful-rise strategy.